Efeito do treinamento muscular excêntrico associado ao treinamento da flexibilidade nas propriedades musculotendíneas e na força muscular - Luiz Antonio Moreira Junior (2010)
The studies that investigated the chronic effects of strength associated with flexibility training performed either concentric and eccentric actions or only isometric actions. Knowing that the strength training adaptations are related with the type of muscle action performed and that eccentric actions may improve the flexibility performance, the aim of this study is to analyze the effects of six weeks of eccentric training with different range of motion associated or not to flexibility training of hamstrings muscles on strength and flexibility parameters. Participated of this study 36 male subjects allocated randomly in three groups: control (CON), eccentric with full knee range of motion (FE) and eccentric with partial knee range of motion (PE). Each leg of experimental groups was submitted to specific training, resulting four subgroups: PE, eccentric with partial knee range of motion; PE_F, eccentric with partial knee range of motion plus flexibility training; FE, eccentric with full knee range of motion; FE_F, eccentric with full knee range of motion plus flexibility training. Strength and flexibility parameters were assessed before and after training. After training there were significant differences on most parameters assessed, except stiffness and energy. The maximum range of motion, maximum passive torque and stretching tolerance passive torque and range of motion significantly increased to PE_F and FE_F. These results were not found for PE and FE. Only FE increased significantly maximum range of motion and passive torque on stretching feeling, while PE did not show significant differences for these parameters. The FE and FE_F significantly increased maximum range of motion, but the increase shown by FE_F was significantly higher (29%) than FE (13%). Based on PE and PE_F results, it is clear that flexibility training performed by PE_F was the main reason for this result, since PE did not show any difference on parameters evaluated. The results demonstrated that PE_F and FE_F maximum range of motion increase was the result of an increase on stretch tolerance without changes on viscoelastic properties of muscle tendon unit. A reason to FE maximum range of motion increase remains unclear, since maximum passive torque did not change for this subgroup. The one maximum repetition performance increased for PE and FE, and the strength performance assessed on the maximum voluntary contraction test increased for PE_F, FE and FE_F. No significant differences were found on integrated electromyography to any subgroup. Based on this study we can conclude that flexibility training can significantly change most of the parameters studied, without negatively affecting the increase in muscle strength. The eccentric training through different range of motion resulted in distinct changes at the flexibility parameters.